Retrospective Assessment of the Anatomy and Dimensions of Nasopalatine Canal with Cone-Beam Computed Tomography - Keskek, Ceren Ozeren; Aytugar, Emre; Cene, Erhan (UAB Stilus Optimus, 2022)
Objectives: The objective of this retrospective study was to evaluate the anatomy and morphology of the nasopalatine canal in axial, sagittal, and coronal sections with cone-beam computed tomography and to appraise the effect of gender, age, and dental status on the nasopalatine canal. Material and Methods: Overall 1000 patients with cone-beam computed tomography (CBCT) images were analysed retrospectively. The morphology of the nasopalatine canal (NPC) was classified according to sections. Its sizes were measured, and variations were evaluated. The variables obtained were statistically analysed. Results: It was observed that the most common NPC shape was the cylindrical type (47.1%) in sagittal sections, and the C-shaped canal (51.1%) in coronal sections. In the axial section, two Stenson foramen (45.2%) were observed most frequently, and the most common form was found as oval (60.7%). In sagittal sections, statistically significant differences were obtained between all morphometric measurements and shapes of the NPC except the angle of the canal. It was found that all morphometric measurements in sagittal and coronal sections were higher in men. Also, it was found that the NPC angle and NPC length decreased with tooth loss. Conclusions: The nasopalatine canal shows many variations, and its dimensions differ according to gender, age, and dental status. For this reason, before the surgical procedures are applied to the maxilla, it should be evaluated radiologically to prevent complications.
Keywords: anatomy; cone-beam computed tomography; maxilla; radiology; MORPHOLOGY; Dentistry, Oral Surgery & Medicine